Integrating miRNA and mRNA Profiling to Assess the Potential miRNA–mRNA Modules Linked With Testicular Immune Homeostasis in Sheep - Li, Taotao; Wang, Xia; Luo, Ruirui; An, Xuejiao; Zhang, Yong; Zhao, Xingxu; Ma, Youji (Frontiers in Veterinary Science, 2021)
Testicular immune privilege is essential for protecting auto-antigenic germ cells especially meiotic and post-meiotic germ cells from systemic immune response, thus creating a homeostatic immune microenvironment for normal spermatogenesis. Despite its importance, the regulation of this privilege in sheep, an important agricultural animal, is poorly understood. To better understand the roles of mRNAs/miRNAs involved in this privilege, in this study, a systematic expression profiling of mRNAs and miRNAs on testicular tissues derived from pre-pubertal and post-pubertal Tibetan sheep was assessed by mRNA- and miRNA-sequencing. Here, we identified 1,118 differentially expressed (DE) mRNAs associated with immunity (245 up- and 873 down-regulated) and 715 DE miRNAs (561 up- and 154 down-regulated) in post-pubertal testis compared with pre-puberty. Functional enrichment analysis indicated that DE mRNAs mainly enriched in biological processes or pathways strongly associated with blood-testis-barrier (BTB) function, and many down-regulated mRNAs with low abundance expression significantly enriched in pathways related to immune response. Also, multiple key miRNA-target negative correlation regulatory network were subsequently established. Finally a putative schematic model of miRNA-mRNA-pathway network mediated by immune homeostasis-related genes was thus proposed to intuitively show their potential regulatory roles in sheep testicular privilege. Taken together, we conclude that identified many immune-related genes are negatively regulated by potential miRNAs to participate in the homeostatic regulation of testicular immune privilege of sheep through sustaining BTB function and inhibiting immune responses under normal physiological status. This work offers the first global view of the expression profiles of miRNAs/mRNAs involved in sheep testicular immune privilege and how the genes potentially contribute to the immune-homeostatic maintenance.